Educational interventions for coronary artery bypass grafting: reducing anxiety and supporting recovery – a narrative review - Hamzah, Siti Aishah; Daud, Azlina; Jamaludin, Thandar Soe Sumaiyah; Mohd Mokhtar, Hanida Hani; Haron, Zarina (IIUM Press, 2025)
Background: To review evidence on educational interventions for patients undergoing coronary artery bypass grafting (CABG), with particular emphasis on educational materials such as oral explanations, videos, and other multimedia approaches, and their impact on anxiety and depression. Methods: A narrative synthesis was conducted of 19 empirical studies, including randomised trials, quasi-experimental designs, feasibility studies, and pilot projects. Interventions covered preoperative nurse-led explanations, videos, peer-narrated clips, virtual reality tours, simulation training, smartphone or web applications, and combined education with relaxation, music, or massage. Outcomes of interest were measures of anxiety and depression, patient knowledge and satisfaction, and recovery outcome. Results: Structured educational interventions consistently reduced preoperative anxiety across multiple settings. Video, audiovisual, and simulation formats produced reliable gains in patient knowledge and satisfaction and were often preferred to verbal or written information alone. Programmes that combined education with calming or practical supports (for example, music, relaxation, or simulation) produced larger effects on anxiety and some physiological markers. Longer or continuous interventions (web/app-based follow-up, counselling) showed greater reductions in depressive symptoms than single-session approaches. Several eHealth programmes reduced unplanned health care contacts and sped patient-reported recovery, but effects on hard clinical endpoints (ICU stay, readmission, mortality) were inconsistent. Conclusion: Educational interventions, especially multimedia and hybrid models, help reduce anxiety and improve knowledge and recovery experience for CABG patients. Larger studies involving multiple centres with standardised outcomes and longer follow-up are needed to clarify effects on depression and clinical endpoints